2019
DOI: 10.21608/ejrs.2019.45676
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using Onion Seed and Moringa Seed Oil on Productive and Physiological Performance of Growing Rabbits Under Hot Climate Conditions.

Abstract: A completely random experiment was conducted to evaluate onion and moringa seed oils or their mixture under climate summer conditions on growth performance, carcass traits, rectal temperature, respiration rate, blood biochemistry, digestibility coefficients, and economic efficiency of growing rabbits, from June, to August, 2015.A total of 108 Bauscat rabbits, weaned at 5 weeks of age with an average initial body weight of 528.80 ± 1.49,g were randomly distributed into four experimental treatments (27 rabbits/ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Oral administration of RSO, WGO, and their mixture improved the serum total protein as well as albumin and globulin levels compared to the control group. In agreement with the current results, the serum total protein as well as albumin and globulin levels improved significantly (p ≤ 0.05) when the rabbits were given the mixture of moringa oil and RSO, followed by individual moringa oil and RSO supplementation or growing rabbits that received moringa oil alone or with onion oil [70,71]. The significant increase in serum total protein and albumin observed in rabbits that were administered orally with RSO, WGO, and their mixture indicated the ability of these oils to stimulate the regeneration of hepatic tissue, which increased protein synthesis in the liver and improved the functional status of the liver cells [12,83] or these oils had a positive effect on thyroid hormone secretion, which could affect the metabolism of nutrients (Table 5).…”
Section: Serum Biochemical Parameterssupporting
confidence: 88%
See 1 more Smart Citation
“…Oral administration of RSO, WGO, and their mixture improved the serum total protein as well as albumin and globulin levels compared to the control group. In agreement with the current results, the serum total protein as well as albumin and globulin levels improved significantly (p ≤ 0.05) when the rabbits were given the mixture of moringa oil and RSO, followed by individual moringa oil and RSO supplementation or growing rabbits that received moringa oil alone or with onion oil [70,71]. The significant increase in serum total protein and albumin observed in rabbits that were administered orally with RSO, WGO, and their mixture indicated the ability of these oils to stimulate the regeneration of hepatic tissue, which increased protein synthesis in the liver and improved the functional status of the liver cells [12,83] or these oils had a positive effect on thyroid hormone secretion, which could affect the metabolism of nutrients (Table 5).…”
Section: Serum Biochemical Parameterssupporting
confidence: 88%
“…In parallel to our results, using onion or moringa oils or a mixture of them significantly (p ≤ 0.05) improved digestibility coefficients of CP and EE compared to the control group. Meanwhile, the digestibility of DM, OM, CF, and NFE was not affected significantly by the addition of different oils [70,71]. In this line, the addition of 1 g RSO/kg diet or 1 g onion seed oil/kg diet and their combination in the growing rabbit's diet increased (p ≤ 0.05) the digestion coefficients of CP and EE compared to the control group [17].…”
Section: Digestion Coefficients Of Nutrient Nutritive Values and Nitrogen Balancementioning
confidence: 99%
“…Spraying Japanese quail eggs with natural disinfectants or natural oils as natural disinfectants (pre-incubation) is a good way to improve the growth performance (feed intake, body weight and body weight gain) of chicks at 14 days of age and improved feed conversion as reported by Abdel-Hafez, 2017 andFouad et al, 2018). Sayed Ahmed et al, (2019) found that the dietary Moringa oil supplementation may help overcome the negative effects of heat stress on growth performance…”
Section: Growth Performancementioning
confidence: 93%
“…There was a non-significant difference in counts of different white blood cells (%) in chicks (Table 8). Sayed Ahmed et al, (2019) noted that total blood protein and globulin were significantly increased (P≤0.05) due to dietary Moringa oil compared to the control group. However, the globulin level has been used as an indicator of increased immunity and a source of antibody production.…”
Section: Blood Constituentsmentioning
confidence: 98%